Efficacy of one-step-ultrasonic route to producing hydroxyapatite nanoparticles from cockle shells - Hasan, Mohamad Rais; Abdullah, Che Azurahanim Che; Nor Afizah, Mustapha; Ghazali, Mohd Sabri Mohd; Noranizan, Mohd Adzahan (Institution of Chemical Engineers, 2024)
Seafood products have contributed significantly to the world's source of dietary protein and various nutrients. Developing an innovative seafood product (ISP) such as calcium hydroxyapatite (HAp) provides a high-nutrient ingredient for foods and seafood. Despite the potential of this ISP as an ingredient, the conventional processing approach requires multiple steps, high energy, and raw materials usage to produce mediocre products. This study aims to evaluate the efficacy of ultrasound in facilitating the HAp extraction process. Samples were separated into ultrasonication (low-intensity= 0.18 W/cm2, moderate-intensity 0.35 W/cm2, and high-intensity= 0.41 W/cm2 at 37 kHz for 15 mins) and without ultrasonic treatments, with the same technique. The efficacy of the extraction process was analyzed in terms of the yield percentage, whiteness index (WI), morphological characteristics, particle size distribution, elemental composition, crystallinity phase, degree of crystallinity, and crystallite size. The low-intensity and moderate-intensity ultrasonication significantly reduces the WI and yield of HAp obtained. The high-intensity ultrasonication did not significantly affect yield, WI, and growth orientation. However, it reduces particle size from 200 to 550 nm to 26–42 nm, and narrowing the distribution range. Crystallinity is also significantly improved by ultrasonic energy, from 61 to 79, with a slightly larger crystal size (24 nm) than without ultrasound. Findings on a novel cost-effective approach and ultrasonic effect seem relevant for other extraction systems of different biomaterials.